2017
DOI: 10.1111/jog.13476
|View full text |Cite
|
Sign up to set email alerts
|

Maternal peripartum septic shock caused by intrauterine infection with Edwardsiella tarda: A case report and review of the literature

Abstract: Edwardsiella tarda (E. tarda) is a rare pathogen in humans, especially during the peripartum period. Only a few cases of fatal neonatal infection with E. tarda have been reported. Herein, we describe a case of maternal septicemia caused by E. tarda following peripartum chorioamnionitis. The mother developed septic shock, disseminated intravascular coagulation and a post-cesarean wound hematoma with abscess. Her condition improved with multidisciplinary therapy including blood transfusion, antimicrobial agents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…1 Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur. [2][3][4][5][6][7][8] Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50%. [9][10][11] Predisposing illnesses include diabetes, hepatobiliary and bowel diseases, sickle cell disease, and immunodeficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur. [2][3][4][5][6][7][8] Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50%. [9][10][11] Predisposing illnesses include diabetes, hepatobiliary and bowel diseases, sickle cell disease, and immunodeficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Edwardsiella species are generally found in marine animals and their habitats, but humans may be incidentally infected through exposure to water environments or ingestion of contaminated raw seafood 1 . Although the gastrointestinal tract is the site most often involved (presenting as a self-limited gastroenteritis), other manifestations such as pelvic or intra-abdominal abscesses, vertebral osteomyelitis and epidural abscess, wound infections and myonecrosis, and bacteremia can occur 2–8 . Systemic infection usually presents in patients with underlying chronic conditions, and mortality rates in these patients can be as high as 50% 9–11 .…”
Section: Discussionmentioning
confidence: 99%
“…E. tarda can also cause bloodstream infections and septic shock, with a poor prognosis. The mortality of septicemia caused by E. tarda infection is 38% [ 3 6 ]. Therefore, E. tarda bloodstream infections are dangerous and acute, which is relevant in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…Edwardsiella tarda is a gram-negative, facultative anaerobe that is a member of the family Enterobacteriaceae and was first described by Ewing et al in 1965 [ 1 ]. Since then, a growing body of literature has reported E. tarda isolates particularly related to brackish water and marine ecosystems, including reptiles, amphibians, and fish [ 2 ]. E. tarda human infections are rare and mainly present as gastroenteritis; however, extraintestinal and systemic infections have been reported that, when present, are a potentially life-threatening condition carrying up to 50% risk of mortality [ 3 ].…”
Section: Introductionmentioning
confidence: 99%